Straits settlements Blue Book (imports/exports) 1893-1894 vol.32-33 (Great Britain : Public Record Office, 1971)
Mengandungi'Recapitulatory and comparative statement of the value of imports into and exports from the Colony of the Straits Settlements during the year 1893';'Blue Book 1894;'Straits Settlements return of imports and exports for the year 1894'.